(untitled) (Journal of Parents and Teachers, 2026)
Sant Ignasi School designed a programme for the social education of pupils, with the aim of fostering a sense of justice and raising awareness of social exclusion. Pupils undertook six months of voluntary work in various areas. The programme proved highly successful, as it not only increased interest in social issues but also strengthened the pupils’ desire to continue with social work.